THE EFFECT OF INQUIRY TRAINING LEARNING MODEL TO STUDENT LEARNING OUTCOMES ON ELASTICITY AND HOOKE’S LAW MATERIAL - Yeni Megalina; Emil Sandi (Jurnal Pendidikan Fisika, 2019)
This research aims to determine the effect of inquiry training learning model to student learning outcomes on elasticity and Hooke’s law subject matter. This research is quasi-experimental design with two control group pretest-posttest. With random cluster sampling technique by taking two classes of fourth grade is class X MIA-4 as the experimental class and class X MIA-3 as the control class with each numbered 30 people. The research instruments used in the form of test results in cognitive learning form description consists of 7 questions that have been validated and observation sheet to assess the activities. The result showed an average value 29,00 pretest experimental class and control class pretest 28,05. After the treatment si given experimental class with inquiry training learning model and control class with conventional learning the data obtained with the posttest average yield experimental class and control class was 73,95 and 59,62. Development activity of experimental class gained an average categorized as  active. Based on the results of hypothesis testing using different test (t -test) obtained the influence of inquiry training learning model on student learning outcomes in a elasticity and Hooke’s law material of class XI in the SMA Swasta Dharma Pancasila Medan